Exploring Numeracy Games as an Ice-Breaking Strategy: Impact on Mathematics Learning Achievements - Jumrah, Jumrah (FKIP Universitas Mataram, 2025)
students frequently perceive it as intimidating, monotonous, and challenging. Indonesian learners achieved merely 366 points in mathematics assessments, representing a decline from previous PISA evaluations between 2015-2018. This performance falls substantially below the standard range of 465-475 points, primarily due to widespread negative attitudes toward mathematics among students. Students' lack of enthusiasm for mathematical studies creates aversion and anxiety, hindering their learning experience. To combat these negative emotions, educators must implement engaging teaching strategies that promote comfort and relaxation during instruction. Ice-breaking techniques represent one effective approach, particularly when incorporating educational games that combine entertainment with learning objectives. Numeracy games offer an excellent ice-breaking method, allowing students to grasp fundamental mathematical principles while enjoying interactive activities. This research investigates how ice-breaker techniques using numeracy games enhance academic achievement among eighth-grade students. The study utilized a pre-experimental design with a single experimental group to evaluate the ice-breaker method's effectiveness on mathematics performance in class VIII.2 at SMP Negeri 2 Patampanua. Employing a quantitative experimental methodology, researchers conducted a one-group pretest-posttest analysis within the same classroom setting. Results demonstrate that ice-breaker strategies incorporating numeracy games significantly improve mathematics learning outcomes for students in the examined class, suggesting this approach effectively addresses traditional barriers to mathematical education